Media coverage and pandemic behaviour: Evidence from Sweden - Marcel Garz; Maiting Zhuang (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2022)
We study the effect of media coverage on individual behaviour during a public health crisis. For this purpose, we collect a unique dataset of 200,000 newspaper articles about the Covid-19 pandemic from Sweden - one of the few countries that did not impose mandatory lockdowns or curfews. We show that mentions of Covid-19 significantly lowered the number of visits to workplaces and retail and recreation areas, while increasing the duration of stays in residential locations. Using two different identification strategies, we show that these effects are causal. The impacts are largest when Covid-19 news stories are more locally relevant, more visible and more factual. We find larger behavioural effects for articles that reference crisis managers (as opposed to medical experts) and contain explicit public health advice. These results have wider implications for the design of public communications and the value of the local media.
Keywords: D83; H12; I12; I18; J22; L82; 330; Covid-19; Mobility; Newspapers; Persuasion; Public health